2016
DOI: 10.1093/ehjci/jew139
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial fat volume is related to atherosclerotic plaque burden rather than to lesion severity

Abstract: The main finding of the present study was the identification of PFV as more closely related to atherosclerotic plaque burden rather than to lesion severity in patients referred to invasive coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
9
0
2
Order By: Relevance
“…Several investigations have bestowed PAT a major role in the development and progression of coronary atherosclerosis, related to vasocrine and paracrine signaling that leads to the influx of pro-inflammatory adipokines. Furthermore, the local effect of PAT was demonstrated by studies showing an increased risk for atrial fibrillation, and left ventricular remodeling and dysfunction (1,3,5,2224).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations have bestowed PAT a major role in the development and progression of coronary atherosclerosis, related to vasocrine and paracrine signaling that leads to the influx of pro-inflammatory adipokines. Furthermore, the local effect of PAT was demonstrated by studies showing an increased risk for atrial fibrillation, and left ventricular remodeling and dysfunction (1,3,5,2224).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, case-control studies identified pericardial fat volume as a strong predictor of myocardial ischemia (113,305). By contrast, some studies did not find such an association between EAT and the extent of CAD in intermediate to high risk patients, suggesting that the relationship is not constant at more advanced stages (263,306). Interestingly, in the positive studies linking EAT with CAD and developing high risk obstructive plaques, the association was independent of adiposity measures, BMI and the presence of coronary calcifications (128,136).…”
Section: Histological and Radiological Evidencementioning
confidence: 99%
“…Such inconsistent or controversial relationships might be due to lack of dividing the patients according to BMI degree, as the pathophysiological interaction between increased PFV and coronary atherosclerosis burden may be associated with various metabolic and circulatory factors of obesity. 3,7,8 To address the potential confounding effect of BMI grades on the association of PFV with coronary atherosclerosis burden, we aimed to assess the possible relationships of PFV measured by multi-detector CT (MDCT) angiography with coronary atherosclerotic markers (coronary artery calcium score [CAC], plaque, and luminal stenosis) among BMI categories.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several clinical studies reported inconsistent results regarding the association of increased pericardial fat deposition with coronary atherosclerotic markers. Such inconsistent or controversial relationships might be due to lack of dividing the patients according to BMI degree, as the pathophysiological interaction between increased PFV and coronary atherosclerosis burden may be associated with various metabolic and circulatory factors of obesity 3,7,8 …”
Section: Introductionmentioning
confidence: 99%